2019
DOI: 10.1111/all.13873
|View full text |Cite
|
Sign up to set email alerts
|

Only α‐Gal bound to lipids, but not to proteins, is transported across enterocytes as an IgE‐reactive molecule that can induce effector cell activation

Abstract: BackgroundThe oligosaccharide galactose‐α‐1,3‐galactose (α‐Gal), present in mammalian proteins and lipids, causes an unusual delayed allergic reaction 3 to 6 hours after ingestion of mammalian meat in individuals with IgE antibodies against α‐Gal. To better understand the delayed onset of allergic symptoms and investigate whether protein‐bound or lipid‐bound α‐Gal causes these symptoms, we analyzed the capacity of α‐Gal conjugated proteins and lipids to cross a monolayer of intestinal cells.MethodsExtracts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 47 publications
0
64
2
2
Order By: Relevance
“…Humans evolved with the inactivation of the α1,3-GalT gene, which resulted in the recognition of the carbohydrate α-Gal as a non-self-antigen, thus inducing the production of high antibody titers against this molecule (Galili, 2018). This evolutionary trait benefits humans by providing immunity to pathogens containing α-Gal in the surface while increasing the risks of developing the AGS triggered by the IgE antibody response against α-Gal present in glycoproteins and glycolipids from tick saliva and tissues of non-catarrhine mammals (Commins et al, 2009;Van Nunen et al, 2009;Platts-Mills et al, 2015;Steinke et al, 2015;Galili, 2018;Cabezas-Cruz et al, 2019;de la Fuente et al, 2019;Hilger et al, 2019;Román-Carrasco et al, 2019;Park et al, 2020). The AGS is characterized by delayed anaphylaxis to red meat consumption and immediate anaphylaxis to tick bites, xenotransplantation, and certain drugs such as cetuximab (Mateos-Hernández et al, 2017;Hilger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Humans evolved with the inactivation of the α1,3-GalT gene, which resulted in the recognition of the carbohydrate α-Gal as a non-self-antigen, thus inducing the production of high antibody titers against this molecule (Galili, 2018). This evolutionary trait benefits humans by providing immunity to pathogens containing α-Gal in the surface while increasing the risks of developing the AGS triggered by the IgE antibody response against α-Gal present in glycoproteins and glycolipids from tick saliva and tissues of non-catarrhine mammals (Commins et al, 2009;Van Nunen et al, 2009;Platts-Mills et al, 2015;Steinke et al, 2015;Galili, 2018;Cabezas-Cruz et al, 2019;de la Fuente et al, 2019;Hilger et al, 2019;Román-Carrasco et al, 2019;Park et al, 2020). The AGS is characterized by delayed anaphylaxis to red meat consumption and immediate anaphylaxis to tick bites, xenotransplantation, and certain drugs such as cetuximab (Mateos-Hernández et al, 2017;Hilger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In all mammals except old world monkeys and humans, aGal is produced by an alpha-1,3-galactosyltransferase, which is mutated in humans [20,60]. A recent study proposed that RMA is elicited by glycolipids containing aGal but not by glycoproteins due to the difference in transport across the gut cell layer [61]. However, the nature of RMA sensitizers, likely originating from tick salivary secretion, needs to be further investigated.…”
Section: Agal In the Tick Sg As The Sensitizer Of Red Meat Allergymentioning
confidence: 99%
“…While most ingested proteins are transported to the bloodstream within 1–2 h after ingestion, the majority of lipids enters the blood as part of chylomicrons around 4 h postmeal ( 64 ). Indeed, using proteins and lipids extracted from grilled beef, Roman-Carrasco et al demonstrated that alpha-gal containing glycolipids but not -proteins were able to cross a monolayer of intestinal cells as part of chylomicrons ( 65 ). As relevant alpha-gal carrying allergens in pork kidney, angiotensin-I-converting enzyme (ACE I) and aminopeptidase N (AP-N) have been identified ( 66 ).…”
Section: Carbohydrates As Important Epitopes In Type I Allergymentioning
confidence: 99%